Synthesis, characterization and dispersion stabilities of novel ionic and nonionic diol modified waterborne polyurethane dispersions with different polyols - Pamir, Ozgur; Ocal, Nuket; Aydogan, Feray (TAYLOR & FRANCIS INC, 2023)
Several high solid content waterborne polyurethane dispersions (WPUDs) with the combination of anionic and nonionic stabilization were synthesized by polyaddition reaction using isophorone diisocyanate (IPDI), trimethylol propane (TMP) and 1,6-hexanediol (HDO) as the hard segments, polypropylene glycol with molecular weight of 2000 Da (PPG-2000), and polytetramethylene ether glycol with molecular weight of 2000 Da (PTMG-2000) as the soft segments, anionic diol dimethylol propionic acid (DMPA) and nonionic diol Y-mer N 120 (NID) as the donors of hydrophilic groups. The chain extension reaction between residual NCO groups was made by using hydrazine (HYD). The effects of the combination of anionic and nonionic monomer and macrodiol types on the performance of the WPUDs were studied in terms of particle size distribution and dispersion stability. The results showed that the WPUDs exhibited narrow particle size distribution, good appearance and good mechanical properties.
Keywords: Waterborne polyurethane; nonionic and ionic dispersing monomers; dispersion stability; nonionic diol; high solid content; Turbiscan Lab (R) Expert; MOLECULAR-WEIGHT; CHAIN EXTENSION; SOLID CONTENT; MACRODIOL; EXTENDER; CAST; Chemistry